SISTEM PAKAR DIAGNOSIS PENYAKIT PADA REPTIL DENGAN METODE CERTAINTY FACTOR BERBASIS ANDROID - Donny Oktavian; Annurrullah Fajrin, Alfannisa (LPPM Universitas Putera Batam, 2025)
Reptiles likes turtles, snakes, and iguana are becoming popular pets due to their unique traits and easy care. However, limited information and shortage of specialized veterinarians in rural areas hinder early disease detection and management. This study develops an expert system for diagnosing reptile diseases using the Certainty Factor (CF) method on Android. The system helps pet owners recognize early symptoms and suggests initial treatments. Evaluation shows the system accurately identifies diseases based on user-inputted symptoms, with a confidence level. The CF method effectively manages uncertainty by combining values from multiple symptoms, achieving over 90% accuracy compared to manual diagnosis. The application has a user friendly interface and quick response time, but its knowledge base is currently limited and does not cover all known reptile diseases.